simplify the following :
plz please do this please
Attachments:
![](https://hi-static.z-dn.net/files/d67/b1f64ce44e0fd7ef3aaee9d68e7f0127.jpg)
Answers
Answered by
1
heya answer is here........
Attachments:
![](https://hi-static.z-dn.net/files/dc1/8acc7deba082213d42844619ca16d5b7.jpg)
Answered by
1
As we know that ,
(a-b)(a+b) = a²-b²
Using the same formula as above :-
(a²-b²)(a²+b²) -(a²-b²)²
= a⁴-b⁴- a⁴-b⁴+2a²b²
= -2b⁴+2a²b²
= 2b²(-b²+a²).
(a-b)(a+b) = a²-b²
Using the same formula as above :-
(a²-b²)(a²+b²) -(a²-b²)²
= a⁴-b⁴- a⁴-b⁴+2a²b²
= -2b⁴+2a²b²
= 2b²(-b²+a²).
Anonymous:
:-)
Similar questions